Home Alone: Widows' Well-Being and Time - Maja Adena; Daniel S. Hamermesh; Michal Myck; Monika Oczkowska (Institute of Labor Economics (IZA), 2021)
Losing a partner is a life-changing experience. We draw on numerous datasets to examine differences between widowed and partnered older women and to provide a comprehensive picture of well-being in widowhood. Most importantly, our analysis accounts for time use in widowhood, an aspect which has not been studied previously. Based on data from several European countries we trace the evolution of well-being of women who become widowed by comparing them with their matched non-widowed 'statistical twins' and examine the role of an exceptionally broad set of potential moderators of widowhood's impact on well-being. We confirm a dramatic decrease in mental health and life satisfaction after the loss of partner, followed by a slow recovery. An extensive set of controls recorded prior to widowhood, including detailed family ties and social networks, provides little help in explaining the deterioration in well-being. Unique data from time-diaries kept by older women from several European countries and the U.S. tell us why: the key factor behind widows' reduced well-being is increased time spent alone.
Keywords: I31; I19; J14; 330; widowhood; well-being; social networks; time use